KAJIAN INFOGRAFIS KEBUDAYAAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Wahyuni, Sri; Susilo, Susilo (Pringgitan, 2023)
This research aims to find out about the presentation of cultural infographic data in the Special Region of Yogyakarta. The discussion in this research will focus on cultural infographic data in the Special Region of Yogyakarta. The method used in this research is a qualitative approach with descriptive method. Data collection was done by interview, observation and documentation. The results show that the presentation using infographics will be very easy to understand in reading secondary data. The results of this study indicate that infographics as promotional media play a role in knowledge utilization. With research indicators, namely attractiveness, clarity of infographics, ease of understanding. So from the results of the study it can be concluded that infographics as a promotional media has a role in the utilization of data presentation: seen in the aspect of attractiveness, it can be concluded that the presentation of the content in infographics attracts the attention of infographic readers through the display of colors and images so as to attract readers' interest; seen from the aspect of clarity, the information presented in infographic content provides clarity to readers through the display of letters and the suitability of the images used; from the aspect of ease, infographic readers can understand the information in infographics easily so that readers can understand the meaning of the message and can interpret it.Keywords:  Infographic, Culture, Tourism